2014
DOI: 10.1016/j.cell.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAc Transferase Enables AgRP Neurons to Suppress Browning of White Fat

Abstract: SUMMARY Induction of beige cells causes the browning of white fat and improves energy metabolism. However, the central mechanism that controls adipose tissue browning and its physiological relevance are largely unknown. Here we demonstrate that fasting and chemical-genetic activation of orexigenic AgRP neurons in the hypothalamus suppress the browning of white fat. O-linked β-N-acetylglucosamine (O-GlcNAc) modification of cytoplasmic and nuclear proteins regulates fundamental cellular processes. The levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
257
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(273 citation statements)
references
References 71 publications
13
257
0
3
Order By: Relevance
“…However, our data provide the first direct correlation between decreased O‐GlcNAc levels and impaired leptin production in vivo. Our findings are in accord with studies showing that reduced O‐GlcNAc lowers levels of Sp1 in cells6f, 13 and that OGT plays a pivitol role in fat tissues 14. Notably, these data also suggest that regulation of leptin by O‐GlcNAc is bidirectional in vivo as overexpression of OGT,3 knockout of OGA,15 and metabolic upregulation of UDP GlcNAc levels16 all increase leptin expression.…”
supporting
confidence: 92%
“…However, our data provide the first direct correlation between decreased O‐GlcNAc levels and impaired leptin production in vivo. Our findings are in accord with studies showing that reduced O‐GlcNAc lowers levels of Sp1 in cells6f, 13 and that OGT plays a pivitol role in fat tissues 14. Notably, these data also suggest that regulation of leptin by O‐GlcNAc is bidirectional in vivo as overexpression of OGT,3 knockout of OGA,15 and metabolic upregulation of UDP GlcNAc levels16 all increase leptin expression.…”
supporting
confidence: 92%
“…In line with this, NPY/AgRP signalling derived from the arcuate nucleus (Arc) inhibits sympathetically innervated BAT thermogenesis through regulation of tyrosine hydroxylase neurons in the hypothalamic paraventricular nucleus (PVN), while alpha-melanocytestimulating hormone (α-MSH) from POMC neurons increases SNS activity and BAT thermogenesis (Yasuda et al 2004, Shi et al 2013. Furthermore, Ruan et al reported that O-GlcNAc transferase (OGT), a rate-limiting enzyme for O-linked β-N-acetylglucosamine (O-GlcNAc) modification of cytoplasmic and nuclear proteins, suppresses browning of WAT and thermogenesis by regulating neuronal excitability in AgRP neurons (Ruan et al 2014). In addition to sympathetic neurons, serotonin (5-HT) neurons were recently reported to recruit and activate brown and beige adipocytes and subsequently regulate glucose and lipid homeostasis (McGlashon et al 2015).…”
Section: Regulation Of Non-shivering Thermogenesismentioning
confidence: 99%
“…Unfortunately, it is not known whether the CNS is implicated in WAT browning regulation during cancer cachexia. Since several obesity studies have identified the hypothalamus as an important regulator of browning (Cao et al 2011, Baboota et al 2014, Beiroa et al 2014, Owen et al 2014, Ruan et al 2014, Dodd et al 2015, future studies to explore the role of the hypothalamus in cachexia-induced browning are encouraged.…”
Section: Neuroendocrine Regulation Of Cachexia-induced Thermogenesis mentioning
confidence: 99%